Meningkatkan Akuntabilitas Pengelolaan Dana BOS : Pelatihan Dasar Manajemen Keuangan bagi Kepala Sekolah dan Bendahara Sekolah di Lingkungan Yayasan Al Mawaddah Warrahmah Kolaka - Sulkifli Ar; Aiedil Pebri Suwarna; Rifaldi Gunawan; Vill Janna Ningzi; Akmir Akmir; Akbar M. Sanusi (Jurnal Pengabdian Masyarakat, 2025)
This community service program aimed to improve the accountability of School Operational Assistance (BOS) fund management through basic financial management training for school principals and treasurers within the Al Mawaddah Warrahmah Foundation in Kolaka. Initial assessments revealed that most participants lacked adequate understanding of systematic budgeting and proper financial recording based on current regulations. Through intensive training and mentoring, participants demonstrated significant improvements in their ability to develop school budgets (RKAS) based on actual needs, manage budget revisions, and operate digital BOS reporting applications (ARKAS and BOP Salur). Beyond technical competencies, the program also fostered greater awareness of the importance of accountability, transparency, and good governance in managing public funds. Institutional impacts included initiatives to establish internal SOPs, improve financial archiving systems, and involve school committees in planning and reporting processes. The foundation responded positively, committing to make similar training an annual agenda and to develop an integrated digital financial monitoring system. Overall, this program successfully laid the groundwork for a culture of professional and responsible school financial management as part of broader efforts to enhance the quality of education.